Ultralow Surface Temperatures in East Antarctica From Satellite Thermal Infrared Mapping: The Coldest Places on Earth - Scambos, T. A.; Campbell, G. G.; Pope, A.; Haran, T.; Muto, A.; Lazzara, M.; Reijmer, C. H.; van den Broeke, M. R. (John Wiley and Sons Inc., 2018)
We identify areas near the East Antarctic ice divide where <−90 °C surface snow temperatures are observed in wintertime satellite thermal-band data under clear-sky conditions. The lowest temperatures are found in small (<200 km2) topographic basins of ~2 m depth above 3,800 m elevation. Approximately 100 sites have observed minimum surface temperatures of ~−98 °C during the winters of 2004–2016. Comparisons of surface snow temperatures with near-surface air temperatures at nearby weather stations indicate that ~−98 °C surfaces imply ~−94 ± 4 °C 2-m air temperatures. Landsat 8 thermal band data and elevation data show gradients near the topographic depressions of ~6 °C km−1 horizontally and ~4 °C m−1 vertically. Ultralow temperature occurrences correlate with strong polar vortex circulation. We discuss a conceptual model of radiative surface cooling that produces an extreme inversion layer. Further cooling occurs as near-surface cold air pools in shallow high-elevation topographic basins, moderated by clear-air downwelling radiation and heat from subsurface snow.
Keywords: air temperature inversion; Antarctica; remote sensing; snow and ice; surface temperature; thermal mapping; Geophysics; General Earth and Planetary Sciences